2017
DOI: 10.1111/bph.13686
|View full text |Cite|
|
Sign up to set email alerts
|

Sitagliptin reduces inflammation, fibrosis and preserves diastolic function in a rat model of heart failure with preserved ejection fraction

Abstract: *These authors contributed equally to this work. †These authors contributed equally to this work and are co-senior authors. BACKGROUND AND PURPOSEHeart failure with preserved ejection fraction (HFpEF) is a systemic syndrome driven by co-morbidities, and its pathophysiology is poorly understood. Several studies suggesting that dipeptidyl peptidase 4 (DPP4) might be involved in the pathophysiology of heart failure have prompted experimental and clinical investigations of DPP4 inhibitors in the cardiovascular sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 99 publications
1
44
0
Order By: Relevance
“…Genetic or pharmacologic inhibition of DPP4 also ameliorated experimental dermal and pulmonary fibrosis induced by bleomycin or in mice with sclerodermatous chronic GvHD. Moreover, a previous study demonstrated that inactivation of DPP4 ameliorated CCL4-induced liver fibrosis and cardiac remodeling after high-salt diet-induced heart failure (43)(44)(45). Targeted inhibition of DPP4 was also shown to reduce scar formation after cutaneous wounds.…”
Section: Discussionmentioning
confidence: 96%
“…Genetic or pharmacologic inhibition of DPP4 also ameliorated experimental dermal and pulmonary fibrosis induced by bleomycin or in mice with sclerodermatous chronic GvHD. Moreover, a previous study demonstrated that inactivation of DPP4 ameliorated CCL4-induced liver fibrosis and cardiac remodeling after high-salt diet-induced heart failure (43)(44)(45). Targeted inhibition of DPP4 was also shown to reduce scar formation after cutaneous wounds.…”
Section: Discussionmentioning
confidence: 96%
“…Sitagliptin, an oral antihyperglycemic agent of the dipeptidyl peptidase‐4 (DPP‐4) inhibitor class reduced cardiac fibrosis in an experimental model of T2DM . Sitagliptin also reduced inflammation, fibrosis and preserves diastolic function in a rat model of HFpEF . The mechanism has been proposed to be operative through operating through insulin‐dependent mechanisms specifically GLP‐1 …”
Section: Oral Hypoglycemic Agents As Potential Therapies For Hfpef Acmentioning
confidence: 99%
“…134 Sitagliptin also reduced inflammation, fibrosis and preserves diastolic function in a rat model of HFpEF. 135 The mechanism has been proposed to be operative through operating through insulin-dependent mechanisms specifically GLP-…”
Section: Oral Hypoglycemic Agents As Potential Therapies For Hfpef mentioning
confidence: 99%
“…Although the present study explores conditions and aspects of DPP4 inhibition that may contribute to unwanted effects of this class of drugs, there is strong evidence that DPP4Is also promote beneficial effects, likely by augmenting cardioprotective hormones such as glucagon-like peptide-1 (GLP-1) (Esposito et al, 2017). As recently reviewed by Nistala and Savin (2017), there is abundant preclinical evidence indicating that DPP4Is protect the heart, vasculature, and kidneys, at least in rodent models of obesity, diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 95%